2013
DOI: 10.3233/jad-130998
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Synaptic Dysfunction in Alzheimer's Disease by Administering a Specific Nutrient Combination

Abstract: Synapse loss and synaptic dysfunction are pathological processes already involved in the early stages of Alzheimer's disease (AD). Synapses consist principally of neuronal membranes, and the neuronal and synaptic losses observed in AD have been linked to the degeneration and altered composition and structure of these membranes. Consequently, synapse loss and membrane-related pathology provide viable targets for intervention in AD. The specific nutrient combination Fortasyn Connect (FC) is designed to ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 173 publications
3
103
0
3
Order By: Relevance
“…Previous studies have shown the potential of these compounds to increase both neurite outgrowth and the number of dendritic spines as well as the levels of pre- or post-synaptic proteins, thus suggesting the ability of Souvenaid™ to improve synaptic structural integrity [2,3,4]. Moreover, Souvenaid™ has been shown to have a positive impact on the cognitive function in patients with mild Alzheimer's disease (AD) [5], pointing to the clinical efficacy of this therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the potential of these compounds to increase both neurite outgrowth and the number of dendritic spines as well as the levels of pre- or post-synaptic proteins, thus suggesting the ability of Souvenaid™ to improve synaptic structural integrity [2,3,4]. Moreover, Souvenaid™ has been shown to have a positive impact on the cognitive function in patients with mild Alzheimer's disease (AD) [5], pointing to the clinical efficacy of this therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the possible clinical usefulness of targeting synaptic dysfunction, the currently available pharmacological options to reach this aim in the clinical setting are limited. Restoring synaptic function, however, represents one of the main targets of nutraceuticals (medical foods), that is, dietary supplements designed to meet the nutritional requirements specifically identified for a clinical purpose [2]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other non-invasive therapies such as music therapy (Balbag, Pedersen, & Gatz, 2015) or multi-nutrient intervention in form of medical foods (Van Wijk et al, 2014;Weiqian, van Wijk, Cansev, Sibjen, & Kamphuis, 2013) can be good protective factors against the development of AD. Table 1 below demonstrates the key benefits and limitations of these therapies in the prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Souvenaid (Nutricia N.V., Zoetermeer, the Netherlands), containing the specific nutrient combination Fortasyn Connect, has been designed to enhance synapse formation and function in AD compared to control product without the specific nutrient [104,105]. Souvenaid is a product intended as a medical food for oral consumption under medical supervision with the purpose of addressing disease-specific nutrient requirements.…”
Section: Aarti and Priyankamentioning
confidence: 99%